Model Tingkat Penerimaan Aplikasi E-Kinerja dengan Metode Theory of Planned Behavior (TPB) - Muttia Ramadhita; Kurniawan; Tata Sutabri; Taqrim Ibadi (STMIK Budi Darma, 2023)
The increasing development of information technology will affect the information system of an agency or company in data management and can present quality information. In accordance with the Circular Letter of the Regional Secretariat No. P-800/60/BKPSDM/2022 concerning Implementation of E-Performance Applications in Planning, Monitoring, Coaching and Evaluation of Employee Performance. The method used in this study is the Theory of Planned Behavior (TPB) approach. So, in order to measure and analyze the level of acceptance of the use of e-performance applications in Sekayu District, adjustments are made to the TPB framework such as adding a moral obligation construct based on the objectives to be achieved by taking into account the TPB instruments. To measure and analyze the relationship between constructs in this study is the Structural Equation Modeling (SEM) approach. The tools for measuring and analyzing the relationship between constructs are with the help of SPSS and PLS software so that the hypotheses that are accepted and rejected, the influence and the percentages as well as the interpretation of the model can be known. The results of this study indicate that the variables of attitude and moral obligations have a positive and significant effect on behavioral interest variables. The behavioral interest variable has a positive and significant effect on the behavioral variable in the acceptance of the use of e-performance applications in Sekayu District. The subjective norm variable and perceived behavioral control, although they have a positive effect on the behavior variable, do not have a significant effect. Thus, the level of acceptance of the use of e-performance applications in Sekayu District is quite acceptable and has been used well by users of e-performance applications in Sekayu District